Corporate governance and compliance of integrated reporting: evidence from Malaysian listed companies / Saiful Bakhtiar Masduki and Mohamad Hafizul Mohd Zaid - Masduki, Saiful Bakhtiar; Mohd Zaid, Mohamad Hafizul (Universiti Teknologi MARA, Perlis, 2019)
Integrated reporting is an emerging practice progressively catching the consideration of organizations. The idea of sustainability reporting increased more significance in the companies’ annual report, a pattern that is implanted likewise in integrated reporting. The governance structure all the more precisely the board of director is the main role to decide whether the company will issue an integrated report. Hence, the purpose of this paper is to examine the relationship between corporate governance (managerial ownership, family ownership, institutional ownership and government ownership) and consistence of coordinated integrated reporting elements disclosure. To achieve this objective, we analysed the way in which integrated reports of 30 companies are following the guidance provided by the International Integrated Reporting Framework (IIRF). As a result, we noticed that most annual report scored the highest compliance level and consistence with the guidance of the IIRF. In addition, the result also demonstrated institutional ownership and government ownership positively affect and significance integrated reporting elements disclosure. Our findings contribute to comprehend the practice of integrated reporting and may have suggestions for regulators in emerging countries for company sustainability reporting